A Systematic Genetic Screen to Dissect the MicroRNA Pathway in Drosophila. - Pressman, S.; Reinke, C.A.; Wang, X.; Carthew, R.W. (G3 : genes - genomes - genetics, 2012)
A central goal of microRNA biology is to elucidate the genetic program of miRNA function and regulation. However, relatively few of the effectors that execute miRNA repression have been identified. Because such genes may function in many developmental processes, mutations in them are expected to be pleiotropic and thus are discarded in most standard genetic screens. Here, we describe a systematic screen designed to identify all Drosophila genes in ?40% of the genome that function in the miRNA pathway. To identify potentially pleiotropic genes, the screen analyzed clones of homozygous mutant cells in heterozygous animals. We identified 45 mutations representing 24 genes, and we molecularly characterized 9 genes. These include 4 previously known genes that encode core components of the miRNA pathway, including Drosha, Pasha, Dicer-1, and Ago1. The rest are new genes that function through chromatin remodeling, signaling, and mRNA decapping. The results suggest genetic screens that use clonal analysis can elucidate the miRNA program and that ?100 genes are required to execute the miRNA program.